Fertility Preferences in Saharsa District (Bihar): A Geographical Study - Mishra, Nitin Kumar (National Geographical Journal of India, 2022)
Fertility preferences in India, expressed in terms of ideal family size and the desire to have additional children, can predict future fertility, with women who have attained or surpassed their ideal family size, or who have explicitly expressed a desire to stop childbearing, less likely than other women to give birth in the future. women will have an unwanted birth is much higher if they have a son than otherwise and as son preference declines, the value of the indicators in predicting the future fertility behaviour of women improves. This paper an attempt to analyze the preferences for family size, sex and the ideal number of the children in population and to suggest some remedial measures to reduce the fertility in general and to enhance human welfare in particular. This study is based on primary data collected through personal survey with the help of a semi-structured questionnaire and interview schedule. The mean ideal number of children varies across the demographic, socio-economic and cultural groups. The mean ideal number of children for the women of 15-19 years is 2 children (1.97 per cent) while it is 3 children (3.05 per cent) for 40-44 years of age. The preference of sons against the daughters is higher in each age group.